(untitled) (Ozone Therapy Global Journal, 2014)
Ozone therapy is today a general medical practice in various countries. A solid basic and clinical research supports the implementation of this procedure. However, for many professionals worldwide it is unknown, tending to classify it as a fraudulent therapy and sometimes dangerous. These comments are so lacking in argument that if they were not made by professionals one could argue that they are ’ gossip ’